Simulação termomecânica de base eólica utilizando concreto álcali-ativado com modelo de dano contínuo - França Filho, Paulo Roberto Pereira de (2024)
The increasing concerns about global warming and climate change have led to a growing focus on sustainability in the construction industry. Cement production, a crucial component of the sector, is one of the major sources of CO2 emissions. This has driven the development of alternatives, such as alkali-activated concrete (AAC), which have garnered interest due to their significant reduction in CO2 emissions and thermal and mechanical properties comparable to conventional concrete (OPC). However, there is no consensus in the literature on how the heat generation of the material should be modeled, as well as its constitutive stress-strain relationships, which complicates standardization and wider application in structures worldwide. The thermomechanical deformations involved in these processes can be sufficient to cause cracking, thereby significantly compromising the structure’s lifespan. One way to analyze the impact of potential material cracking is through continuous damage models, such as the Mazars model. Two subroutines were implemented in the ABAQUS software: one for heat generation (HETVAL) and one for continuous damage of Mazars (UMAT), and a comparative thermomechanical analysis was conducted between the two materials. The response of these materials was studied using a wind tower base model. These structures are typically subjected to complex loads and high temperatures due to exothermic chemical processes during the material’s curing period. It was indicated that the Mazars model can adequately represent the non-linear behavior of AAC. Moreover, the heat generation in AAC, especially with binders composed of fly ash and steel slag, resulted in a significantly lower temperature increase compared to OPC. While in OPC, a damage of 6.5% was simulated before loading and 24% after the load was applied, in AAC no damage was observed during the simulation, resulting in 29% lower stresses. This study suggests that AAC may offer advantages in terms of mechanical performance and durability, particularly in applications with large volumes of concrete.